Considerations for Polymers Used in Ocular Drug Delivery - Allyn, Megan M.; Luo, Richard H.; Hellwarth, Elle B.; Swindle-Reilly, Katelyn E. (Frontiers in Medicine, 2022)
Purpose: Age-related eye diseases are becoming more prevalent. A notable increase has been seen in the most common causes including glaucoma, age-related macular degeneration (AMD), and cataract. Current clinical treatments vary from tissue replacement with polymers to topical eye drops and intravitreal injections. Research and development efforts have increased using polymers for sustained release to the eye to overcome treatment challenges, showing promise in improving drug release and delivery, patient experience, and treatment compliance. Polymers provide unique properties that allow for specific engineered devices to provide improved treatment options. Recent work has shown the utilization of synthetic and biopolymer derived biomaterials in various forms, with this review containing a focus on polymers Food and Drug Administration (FDA) approved for ocular use. Methods: This provides an overview of some prevalent synthetic polymers and biopolymers used in ocular delivery and their benefits, brief discussion of the various types and synthesis methods used, and administration techniques. Polymers approved by the FDA for different applications in the eye are listed and compared to new polymers being explored in the literature. This article summarizes research findings using polymers for ocular drug delivery from various stages: laboratory, preclinical studies, clinical trials, and currently approved. This review also focuses on some of the challenges to bringing these new innovations to the clinic, including limited selection of approved polymers. Results: Polymers help improve drug delivery by increasing solubility, controlling pharmacokinetics, and extending release. Several polymer classes including synthetic, biopolymer, and combinations were discussed along with the benefits and challenges of each class. The ways both polymer synthesis and processing techniques can influence drug release in the eye were discussed. Conclusion: The use of biomaterials, specifically polymers, is a well-studied field for drug delivery, and polymers have been used as implants in the eye for over 75 years. Promising new ocular drug delivery systems are emerging using polymers an innovative option for treating ocular diseases because of their tunable properties. This review touches on important considerations and challenges of using polymers for sustained ocular drug delivery with the goal translating research to the clinic.